2017
DOI: 10.1111/nmo.13273
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrheal effect of sodium hydrosulfide in diabetic rats: In vitro and in vivo studies

Abstract: These findings showed NaHS effectively controlled diarrhea in diabetic rats through decreasing the frequency, and tension of spontaneous contraction of smooth muscles of large, and small intestines. The increased frequency and tension of spontaneous contractions of smooth muscles in diabetic rats may be due to down-regulation of H S biosynthesis enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although different biological effects in some studies, H 2 S is viewed as one of three important gas biological molecules(together with NO and CO). Some studies showed that high concentration H 2 S induce IBD pathogenesis because of making toxicity for cells and genes by upregulating proin ammatory cytokines and damaging mucous layer and epithelial cells [16][17][18]. H 2 S is produced by two ways as biologically endogenous and exogenous ways.…”
Section: Discussionmentioning
confidence: 99%
“…Although different biological effects in some studies, H 2 S is viewed as one of three important gas biological molecules(together with NO and CO). Some studies showed that high concentration H 2 S induce IBD pathogenesis because of making toxicity for cells and genes by upregulating proin ammatory cytokines and damaging mucous layer and epithelial cells [16][17][18]. H 2 S is produced by two ways as biologically endogenous and exogenous ways.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of enteric glial cells may aggravate neuronal loss [1]. Another possible mechanism may be reduced synthesis of sodium hydrosulphide, which acts as an inhibitor of intestinal smooth muscles [45]. There are conflicting results regarding the role of bile acid malabsorption in diabetic diarrhoea, but the theory has recently gained new impetus [12,46].…”
Section: Discussionmentioning
confidence: 99%
“…In the digestive system, CBS exists in the gastric mucosa, colonic epithelium, small intestine, jejunum, and ileum. [30][31][32][33] CBS is also significantly expressed in the spleen. 34 CBS has been suggested to play an important role in the female reproductive system since it is well expressed in the ovary and uterus but is relatively low in the prostate and testis.…”
Section: Enzymes That Synthesize H S 21 | the Distribution Of Cbs And...mentioning
confidence: 99%
“…CBS content in other tissues is relatively low. In the digestive system, CBS exists in the gastric mucosa, colonic epithelium, small intestine, jejunum, and ileum 30–33 . CBS is also significantly expressed in the spleen 34 .…”
Section: Enzymes That Synthesize H2smentioning
confidence: 99%